The sawflies and woodwasps (Hymenoptera: ‘Symphyta’) of Colombia - Malagón-Aldana, Leonardo A.; Smith, David R.; Vilhelmsen, Lars; Serna, Francisco (Zootaxa, 2019)
A survey of the ‘Symphyta’ of Colombia is conducted, based on information from literature as well as on examination of over 2,000 specimens from the major Colombian entomological collections. A total of 127 species are recorded from Colombia, representing six families: Argidae (48 species), Tenthredinidae (37) Pergidae (37), Xiphydriidae (3 species), Siricidae (1 species) and Orussidae (1 species). 11 genera and 68 species are new records for Colombia, doubling the number of previously reported species. Heteroperreyia (Pergidae) is recorded for the first time in northern South America. Most records and species are concentrated in the Andean region. Four new species are described: Acrogymnidia catalina Malagón-Aldana, sp. nov., Ptenos amazonicus Malagón-Aldana, sp. nov. (Argidae), Heteroperreyia andina Malagón-Aldana, sp. nov. (Pergidae) and Derecyrta risaraldensis Malagón-Aldana, sp. nov. (Xiphydriidae). The following taxonomic changes are proposed, and lectotypes designated for all these nominal taxa: Dochmioglene suppar (Konow, 1903), comb. n., Plaumanniana parmata (Konow, 1903), comb. n., and Proselandria analis (Fabricius, 1804), comb. n.; Plaumanniana biclinia (Konow, 1899) = Stromboceros marcidus Konow, 1899, syn. n.; Proselandria analis (Fabricius, 1804) = Stromboceros brevispinis Konow, 1908, syn. n., Monophadnus trichiotomus Cameron, 1911, syn. n. and Romaniola amazonica Forsius, 1925, syn. n.